Immunotherapy for Pediatric Leukemia - Wayne, Alan; Shah, Nirali; Dave, Hema (Frontiers in Oncology, 2013)
Substantial progress has been made in the treatment of leukemia in childhood. Despite this, leukemia remains a leading cause of pediatric cancer-related mortality and the prognosis is guarded for individuals with relapsed or refractory disease. Standard therapies are associated with a wide array of acute and long-term toxicities and further treatment intensification may not be tolerable or beneficial. The curative potential of allogeneic stem cell transplantation is due in part to the graft-versus-leukemia effect, which provides evidence for the therapeutic capacity of immune-based therapies. In recent years there have been significant advances in the development and application of immunotherapy in the treatment of leukemias, including the demonstration of activity in chemotherapy-resistant cases. This review summarizes immunotherapeutic approaches in the treatment of pediatric leukemia including current results and future directions.